Self‐Established Rapid Magnesiation/De‐Magnesiation Pathways in Binary Selenium–Copper Mixtures with Significantly Enhanced Mg‐Ion Storage Reversibility. (14th November 2017) - Zhang, Zhonghua; Chen, Bingbing; Xu, Huimin; Cui, Zili; Dong, Shanmu; Du, Aobing; Ma, Jun; Wang, Qingfu; Zhou, Xinhong; Cui, Guanglei
Abstract: Rechargeable magnesium/sulfur (Mg/S) and magnesium/selenium (Mg/Se) batteries are characterized by high energy density, inherent safety, and economical effectiveness, and therefore, are of great scientific and technological interest. However, elusive challenges, including the limited charge storage capacity, low Coulombic efficiency, and short cycle life, have been encountered due to the sluggish electrochemical kinetics and severe shuttles of ploysulfides (polyselenide). Taking selenium as model paradigm, a new and reliable Mg‐Se chemistry is proposed through designing binary selenium‐copper (Se‐Cu) cathodes. An intriguing effect of Cu powders on the electrochemical reaction pathways of the active Se microparticles is revealed in a way of forming Cu3 Se2 intermediates, which induces an unconventional yet reversible two‐stage magnesiation mechanism: Mg‐ions first insert into Cu3 Se2 phases; in a second step Cu‐ions in the Mg2 x Cu3 Se2 lattice exchange with Mg‐ions. As expected, binary Se‐Cu electrodes show significantly improved reversibility and elongated cycle life. More bracingly, Se/C nanostructures fabricated by facile blade coating Se nanorodes onto copper foils exhibit high output power and capacity (696.0 mAh g −1 at 67.9 mA g −1 ), which outperforms all previously reported Mg/Se batteries. This work envisions a facile and reliable strategy to achieve better reversibility and long‐term durability of selenium (sulfur) electrodes. Abstract : Binary microsized Se‐Cu electrodes show an unconventional yet reversible process occurring in a way of two‐stage magnesiation mechanism: one step is the Mg‐ions inserting into the Cu3 Se2 phases; in the second step Cu‐ions in the Mg2 x Cu3 Se2 lattice exchange with Mg‐ions forming the final products of MgSe nanoparticles and metallic Cu nanowires, resulting in excellent Mg‐ion storage properties.